HEALTHY ENVIRONMENT: A TOOL FOR HEALTH PROMOTION AND LONGEVITY IN NIGERIA - CHUKUMATI, CHRISTIANA NKANUNYE; EKENEDO , GOLDA (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2015)
This work discusses healthy environment as a tool for promoting health in Nigeria. It revealed that human health is very impacted by unsafe environment such as water, air, food and poor housing. Diseases related to polluted drinking water, air, unsanitary food hygiene and poor housing (household environments) constitute a major burden on the health of the people in developing world. Such diseases include- diarrhea, cholera, infective hepatitis, typhoid fever, worms’ infestations, respiratory diseases like asthma, pneumonia, tuberculosis, cross infection amongst others. These contaminants could be physical, biological or chemical their prevention is by health educating the public about high standard of personal and environmental hygiene; provision of portable drinking water as well as proper disposal of waste to improve healthful conditions. Also noted is poor housing to be causes of some respiratory diseases as well as causes of antisocial behavior such as rape and substance abuse. In conclusion, healthy environment is crucial to health. Therefore, individuals, communities and Government should play their respective roles to ensure that our environment is healthy for habitation. It is recommended that Government at all levels should adopt the integrated waste management approach through legislation and implementation. Moral hygiene should be part of school curriculum and non- formal health education should take place at various settings like community gathering. workplace and hospitals to ensure healthy living environment.